2010
DOI: 10.1111/j.1601-5215.2010.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief neuropsychological profiles in psychosis: a pilot study using the Audio Recorded Cognitive Screen (ARCS)

Abstract: The ARCS uses audio administration (approximately 34 min) to reduce clinician time (to 3-5 min for scoring) and appears to be a useful brief assessment tool for examining the cognitive deficits associated with psychosis. However, the potential clinical utility of the ARCS needs to be investigated further in larger samples drawn from a wider variety of specialist and non-specialist settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
4
5
0
Order By: Relevance
“…These results suggest the ARCS is sensitive to the cognitive impairment associated with schizophrenia, with the memory and fluency domains being the main discriminating measures between the two groups. This finding is consistent with the findings of the previous pilot study (26), as well as with the demonstrated pattern of impairment reported in the literature (33). Previous research consistently shows individuals with schizophrenia have significant impairment in memory, attention, and executive functioning, with visuospatial ability and vocabulary the least affected areas of cognition (33).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results suggest the ARCS is sensitive to the cognitive impairment associated with schizophrenia, with the memory and fluency domains being the main discriminating measures between the two groups. This finding is consistent with the findings of the previous pilot study (26), as well as with the demonstrated pattern of impairment reported in the literature (33). Previous research consistently shows individuals with schizophrenia have significant impairment in memory, attention, and executive functioning, with visuospatial ability and vocabulary the least affected areas of cognition (33).…”
Section: Discussionsupporting
confidence: 93%
“…The ARCS and RBANS correlated on memory and overall scores, suggesting a high degree of overlap between the two tests in detecting deficits in these areas as well as a degree of stability in the impairment in memory and overall cognition in this sample (911). The magnitude of the correlations between ARCS and RBANS memory and overall scores were very similar to those demonstrated in the previous pilot study ( r =0.49, r =0.51, respectively) (26). The lack of correlation between ARCS and RBANS visuospatial scores is also consistent with the pilot study, suggesting that the different tasks used to measure visuospatial ability in the ARCS (clock drawing task) and RBANS (complex figure copy and line orientation task) may involve different cognitive processes.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The ARCS possesses a good psychometric profile when compared with other neuropsychological test batteries (Schofield et al, 2013) and has been found to be sensitive to mild cognitive impairment in clinical samples (Lechner-Scott et al, 2010;Loughland et al, 2010;Schofield et al, 2008). The test takes approximately 30 min to complete.…”
Section: Instrumentsmentioning
confidence: 99%